Developing accessible cyberinfrastructure-enabled knowledge communities in the national disability community: theory, practice, and policy. - Myhill WN; Cogburn DL; Samant D; Addom BK; Blanck P (Assistive Technology)
Since publication of the Atkins Commission report in 2003, the national scientific community has placed significant emphasis on developing cyberinfrastructure-enabled knowledge communities, which are designed to facilitate enhanced efficiency and collaboration in geographically distributed networks of researchers. This article suggests that the new cyberinfrastructure movement may not fully benefit those participants with disabilities, unless closer attention is paid to legal mandates and universal design principles. Many technology-enhanced learning communities provide geographically distributed collaboration opportunities that expand the inclusion of diverse peoples and help close the digital divide. However, to date, most collaboratory efforts have not emphasized the need for access among people with disabilities nor meeting minimum standards for technological accessibility. To address these concerns, this article reports on two pilot collaboratory studies that explore the role advanced information, communication, and collaboration technologies play in enhancing geographically distributed collaboration among specific research and applied networks within the national disability community. Universal design principles inform the design of the collaboratory and its use and our efforts to ensure access for all. Data for this article come from Web-based surveys, interviews, observations, computer logs, and detailed, mixed-methods accessibility testing. Emerging results suggest that with deliberate and systematic efforts, cyberinfrastructure can be more accessible and generate benefits among persons with disabilities. The authors provide lessons learned and recommendations for future research, policy, law, and practice.